TRANSCRIPTION FACTORS - Adcock,IM; Ito,K; Caramori,G (2006)
The term ‘transcription factor’ refers to a large family of proteins, which exert transcriptional control via specific interactions with regulatory gene sequences. Here, we provide a summary of the different classes of the transcription factor divided according to their DNA-binding motifs. The modular structure of transcription factors and the presence of distinct interacting domains determine the ability of these factors to associate with each other and with coactivating/repressing proteins. By recruiting transcriptional coactivators, transcription factors can induce changes in chromatin structure enabling gene expression to occur. We use the activation of the Rel transcription factor NF- κB and the nuclear receptor GR as examples to indicate some of the intricacies and subtleties of DNA binding, chromatin remodeling, and transcription factor cross-talk. Finally, we review the evidence for the involvement of select transcription factors in allergic and inflammatory diseases of the lung, and how changes in the expression and/or activity of these factors may vary in disease and provide important targets for future drug development.